METODE DAKWAH USTADZ SUWARDI DALAM MENINGKATKAN SEMANGAT KEAGAMAAN MASYARAKAT KELURAHAN GAJAH SAKTI KABUPATEN BENGKALIS - Afni Yogeta (ADISAM PUBLISHER, 2023)
The method is the path we take to reach the goal. Many businesses will not be successful or will definitely not produce optimal results, if not used the right way Da'wah is an activity or activity inviting to do good which is mainly played by a preacher. Religious enthusiasm is a sense of desire and participation in all religious activities. So the da'wah method is the method used by a preacher to convey da'wah material or a series of activities to achieve certain goals. This study uses qualitative methods in qualitative descriptive techniques, with the research stages namely observation, interview, and documentation, then uses data analysis techniques in the form of words in written and oral form that have been collected previously. So that you know how Ustadz Suwardi's Da'wah Method is in Enhancing the religious enthusiasm of the Gajah Sakti Village Community, Bengkalis Regency